Kebebasan Pers Pasca Orde Baru - - Susilastuti D. N. (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2000)
Freedom of the press suprisingly, demand the existence of controlling capacity of the press. The idea, however, is not to restraint the exercise of the freedom. Rather it is ment to keep thepress maintain its fairness and accuracy, and its commitment to ethical code and law.